1926
DOI: 10.1002/cber.19260590716
|View full text |Cite
|
Sign up to set email alerts
|

Eine Additionsverbindung von Natriummetall an Aluminiumtriphenyl. (Vorläufige Mitteilung.)

Abstract: K r a u s e , PoEccck: Additionsverb. urn Natriummetall. Dahrg. 59 Mit S a l p e t e r s a u r e reagiert das Harz von Ajka leicht und nimmt er-J e 0.36 g Harz ergaben nach $/&dg. Kochen niit HNO, ( d =~. z ) ein gelbes, schwera) Aus Ajkait: 0.1559 g Sbst.: 9.08 ccm N (zzo, 747 mm [korr. 735 mm.).b) Aus S u c c i n i t : 0.3012 g Sbst.: 15.35 ccrn N (zIO, 744 mm [korr. 733 mm]). -heblich mehr Stickstoff auf, als Bernstein: losliches, nicht mehr harzartiges Pulver. 0.1428 g Sbst.: 8.15 ccrn N (24O, 746.7 mm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1926
1926
1989
1989

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Krause and co-workers examined a number of trialkylborines and found that the autoxidation produced either esters of aliphatic boronic acids or the alkylboron oxides (111,112). Johnson and Van Campen postulated in 1938 that the autoxidation proceeds via an intermediate complex, a "borine-peroxide,"…”
Section: Preparation Of Organomercury Peroxidesmentioning
confidence: 99%
“…Krause and co-workers examined a number of trialkylborines and found that the autoxidation produced either esters of aliphatic boronic acids or the alkylboron oxides (111,112). Johnson and Van Campen postulated in 1938 that the autoxidation proceeds via an intermediate complex, a "borine-peroxide,"…”
Section: Preparation Of Organomercury Peroxidesmentioning
confidence: 99%